PERAN LEMBAGA PENDIDIKAN ISLAM PADA DALAM MEMBENTUK GENERASI MUSLIM YANG KOMPETITIF - Sariman, Sariman; Faricha, Faiz (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
Islamic education in Indonesia involves various institutions that play a significant role in nurturing the younger generation, including mosques and pesantren (Islamic boarding schools). This study aims to examine the role of mosques and pesantren as Islamic educational institutions in Indonesian society, as well as their challenges and contributions to educational development. A qualitative approach was used with a literature study, gathering data from various sources including books, journals, and related documents. The research findings show that mosques, in addition to being places of worship, also serve as effective centers of learning for the Muslim community, particularly focusing on education for children and adolescents. On the other hand, pesantren remains a vital educational institution, especially in rural areas, emphasizing religious and character education through traditional approaches. The collaboration between mosques and pesantren was also identified as an important effort to strengthen Islamic education, despite the challenges of modernization and social change that affect their effectiveness. This study suggests the need for enhanced integration between these Islamic educational institutions and adjustments to the changing times to increase the relevance of Islamic education in society.